Examining the views of student midwives and nurses on biochemistry education - Tahiroglu, Veysel (Walter De Gruyter Gmbh, 2023)
Objectives: The aim of this study is to determine the opinions of midwives and nurses about the efficiency and effectiveness of the biochemistry courses they took during their undergraduate education, in the education process and in their fields of study. Methods: Two hundred eighty-four students studying in the department of midwifery and nursing (1-4 classes) participated in this research voluntarily. A questionnaire consisting of 10 multiple-choice questions compiled by the authors with the support of the sociodemographic data form, including age, gender, type of lycee school graduated, and the department they studied, and the literature on biochemistry education were applied to the students. Results: The mean age of the students was 21.25 +/- 0.12. 58.2 % of midwifery department students and 69.1 % of nursing department students reported that biochemistry education is necessary. 64.1 % of midwifery department students and 59.7 % of nursing department students stated that they thought that the biochemistry application course should be absolutely necessary. There was a significant difference between nursing and midwifery students in favor of nursing students in terms of finding the biochemistry course interesting and loving the biochemistry course. A significant difference was found between the two groups in favor of midwifery students in terms of their desire to pursue postgraduate education in biochemistry and to increase biochemistry course hours (p<0.05). Conclusions: It is thought that the results of this study, which include students' opinions, will contribute to the efficiency of biochemistry education and help the lecturer provide a new perspective.
Keywords: biochemistry; education; midwifery; nursing; student